Penerapan Mesin Penyedot Debu Model Sentrifugal Untuk Usaha Kreatif Kerajinan Kulit Kerang Mutiara “Concha” Handycraft Menunjang Pariwisata Berkelanjutan Di Desa Meninting Lombok - Joniarta, I Wayan; Wirawan, Made; Adi Sayoga, I Made; Yudhyadi, I Gusti Ngurah Ketut; Mirmanto, Mirmanto (Jurnal Gema Ngabdi, 2025)
The problem of dust pollution at the service partner "Concha Handycraft" is at the core of program activities. Controlling dust from its source is the main goal, namely replacing blower style vacuum cleaners with centrifugal type vacuum cleaners. The centrifugal type was chosen because it has a simple shape, the motor is separate from the fan, so the motor is protected from dust. The activity method begins with designing, purchasing materials, manufacturing in the workshop, testing, minor repairs, application and assistance. The results obtained are that the centifugal model vacuum cleaner that has been applied has advantages. The electrical power used from previously 260 watts to 120 watts. Working time can also increase because the motor used is a DC motor so it doesn't heat up quickly. If you use a blower model, the electric motor heats up quickly because it gets dust and needs to be cooled. The ability to suck up dust is also increased, with a fan at a 30 degree angle the ability to suck up and throw out is balanced. By using a centripugal model vacuum cleaner, 95% of the dust produced by the grinding machine can be sucked into the dust collection chamber.  Concha Handycraft partner SME owners and employees are very happy with the new machine, so they can be more productive at work, and stay protected from exposure to dust in the workplace.